Single-shot stand-off chemical identification of powders using random Raman lasing - Hokr, Brett H.; Bixler, Joel N.; Noojin, Gary D.; Thomas, Robert J.; Rockwell, Benjamin A.; Yakovlev, Vladislav V.; Scully, Marlan O. (Proceedings of the National Academy of Sciences - PNAS, 2014)
The task of identifying explosives, hazardous chemicals, and biological materials from a safe distance is the subject we consider. Much of the prior work on stand-off spectroscopy using light has been devoted to generating a backward-propagating beam of light that can be used drive further spectroscopic processes. The discovery of random lasing and, more recently, random Raman lasing provide a mechanism for remotely generating copious amounts of chemically specific Raman scattered light. The bright nature of random Raman lasing renders directionality unnecessary, allowing for the detection and identification of chemicals from large distances in real time. In this article, the single-shot remote identification of chemicals at kilometer-scale distances is experimentally demonstrated using random Raman lasing.